Exploring Innovative Work Behaviour Values of Lecturers in the Islamic University in Indonesia - Akh. Yunan Atho'illah; Debby Nindya Istiandari; Ana Toni Roby Candra Yudha; Sherawali Sherawali (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
This study examines the impact of Islamic work ethic, affective commitment, normative commitment, and high-performance work systems on lecturers' performance at 122 State Islamic Universities, 60 Private Islamic Universities, and five private non-Islamic Universities in Indonesia, with a focus on gender differences to enhance the generalizability and accuracy of the findings. Employing the Structural Equation Model Partial Least Squares (SEM-PLS) method, the study tests whether innovative work behaviour mediates these factors. The results reveal that the R-squared value is 0.753. This method reflects that the exogenous variables of Islamic work ethic, affective commitment, and high-performance work system significantly influence innovative work behaviour by 75.3%. However, further findings revealed that the affective commitment of male lecturers does not affect their innovative work behaviour, resulting in reduced innovation and suboptimal performance. Additionally, innovative work behaviour mediates the relationship between Islamic work ethic, affective commitment, high-performance work systems, and lecturers' performance, but not with normative commitment. This plenary paper offers original insights by exploring innovative work behaviour from a gender perspective, a topic that has not been widely covered in previous studies. The research suggests that Islamic Universities should consider gender differences as they promote innovative work behaviours and adopt gender-specific strategies to enhance lecturers' performance. These considerations could foster a more creative and productive work environment. Implications: The study highlights the need for a gender-specific approach to promote innovation and improve lecturers' performance. Further research could explore other factors influencing performance in different cultural and organizational contexts.